Bridging Academia and Society: Institutionalizing Service-Learning Malaysia (SULAM) Within Malaysian Higher Education Frameworks - Vimala, Govindaraju (RSIS International, 2025)
A transformative pedagogy called Service-Learning Malaysia (SULAM) aims to combine academic learning with significant community involvement. SULAM, which is part of Malaysia’s higher education reform agenda, seeks to generate graduates who are civically active, socially conscious, and academically proficient. The institutionalization of SULAM inside Malaysian higher education settings is examined in this research, with an emphasis on how it serves to bridge the gap between academics and society. The study examines how SULAM has been applied across universities, how it aligns with curricular objectives, and how it contributes to graduate outcomes and community development through the use of policy reviews, case analyses, and contemporary studies. SULAM strengthens university-community ties while fostering critical thinking, empathy, and problem-solving skills in students, according to findings. However, obstacles including inconsistent application, scarce resources, and varying faculty preparedness prevent its complete integration. The study emphasizes the necessity of regular evaluation procedures, educator training, and more robust policy support. Malaysian universities can be positioned as proactive contributors to societal issues and the advancement of sustainable national development by institutionalizing SULAM.